REBRANDING STRATEGIES AND MARKET RESPONSE: A CASE STUDY OF LOCAL STARTUPS - Putu Saroyini; M. Joni M. Joni; Fitria Fitria; Eko Wahyu Widayat; Klemens Mere (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Rebranding has become an essential strategy for education technology startups, particularly in highly competitive local markets where differentiation and credibility are crucial. The rapid growth of digital learning platforms, the integration of generative artificial intelligence, and the increasing demand for personalized learning experiences have pushed many startups to reposition their brand identities. Although rebranding is widely practiced, scholarly evidence on its market effects remains scattered, requiring systematic synthesis to inform both theory and practice.This review brings together recent studies published between 2020 and 2025 to analyze rebranding strategies employed by local EdTech startups and the corresponding market responses. It explores how branding adjustments influence adoption, trust, user engagement, and institutional acceptance. The analysis reveals that startups frequently rebrand to communicate innovation, enhance cultural relevance, and build legitimacy in education ecosystems where trust is a critical factor for success.The synthesis indicates that effective rebranding often leads to positive market outcomes such as higher adoption rates, improved customer retention, and strengthened stakeholder confidence. However, cases of user confusion, skepticism, and negative sentiment highlight the risks of poorly executed or inauthentic rebranding.